Internet og multimedia - avmaskuliniseringav IT? - Håpnes, Tove; Rasmussen, Bente (Kvinder, Køn & Forskning, 1998)
When computer technology changes from technology of calculation to the use of text and images in communication, more girls are interested. Girls use computers for at variety of tasks: for writing letters and notes, for chatting on the Internet, for retrieving information for their schoolwork, and for presenting their projects, using graphs and pictures. They are, however, not keen on studying computing, because they are not interested in the technical aspects, and they do certainly not want to sit in front og a computer all day. Women working in computing describe their jobs as social, they work with teams and co-operate with their clients in developing new systems. Nevertheless, their experience has still not changed the general image of the job as being technical and machine-oriented. The technical aspects are absent from their reports but technical knowledgre remains the required tool for getting a job in computing.